MULTI-PURPOSE LAND CONSOLIDATION FOR SUSTAINABLE DEVELOPMENT OF TERRITORIAL COMMUNITIES IN UKRAINE - Stoiko Н.; Cherechon О. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2024)
In Western European countries, modern land consolidation serves as a versatile tool for managing land and spatial planning to facilitate agricultural development, large-scale infrastructure construction, restoration of natural landscapes, biodiversity conservation, and climate change adaptation and mitigation. This study presents a content analysis of textual information on the multi-purpose approach to land consolidation as a land management tool. The aim is to change the ownership structure by redistributing land plots, thereby facilitating the spatial restructuring of rural land use to support the sustainable development of territorial communities in Ukraine. The authors define spatial land use restructuring as an integrated approach to reorganizing rural areas to bring about both quantitative and qualitative changes. The quantitative aspect involves changes in land use, while the qualitative aspect pertains to changes in the ecosystem assets of the community. The study explores the relationship between the sustainable development of territorial communities and the spatial restructuring of land use through land consolidation. It emphasizes the key elements of the multi-purpose land consolidation procedure and analyzes spatial problems related to rural land use in Ukraine. The proposed solutions involve preserving and restoring community ecosystem assets through the withdrawal of erosion-prone areas for conservation transformation, creating ecological networks to establish an integrated environmental infrastructure, and restoring and consolidating forest land. The authors recommend developing a National Land Consolidation Programme, which would integrate land consolidation into the overall land policy of the state. This initiative aims to provide financial, technical, and administrative support for implementing land consolidation projects.